An Analysis of the Genetic Diversity of Bread Wheat x Spelt Breeding Lines in Terms of Their Resistance to Powdery Mildew and Leaf Rust - Klaudia Goriewa-Duba; Adrian Duba; Elżbieta Suchowilska; Marian Wiwart (Agronomy, 2020)
The main aim of this study was to analyze the genetic diversity of breeding lines derived from bread wheat and spelt (bread wheat cvs. Zebra, Torka and Kontesa; spelt breeding lines S10–S14) in terms of their resistance to infections caused by Blumeria graminis f. sp. tritici and Puccinia triticina Eriks. The genomes of all analyzed lines harbored the markers for Pm2a, Pm4b and Pm6a alleles, which confer resistance to the infection caused by B. graminis f. sp. tritici. The markers for Pm4c and Pm4a alleles were also identified in many objects. The high number of Pm markers was noted in the crosses Zebra × S11 and Zebra × S12 whose genomes harbored the markers for Pm2a, Pm3d, Pm4a-4c and Pm6. Most of the studied lines harbored the marker linked to the Lr10 gene, which encodes resistance to the infection caused by P. triticina in wheat. The analysis of the presence of markers linked to the resistance to infections caused by B. graminis f. sp. tritici and P. triticina demonstrated that Zebra × S12 was the most promising breeding line with the highest number of markers for genes/alleles encoding resistance to powdery mildew and leaf rust. This breeding line was also highly resistant to both pathogens under field conditions.